Food Preservation in Developing Countries: Challenges and Solutions - Joardder, Mohammad U. H.; Hasan Masud, Mahadi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This text identifies common mistakes and challenges in food preservation in developing countries, offering solutions which can play a significant role in reducing food waste in these countries. The book offers critical analysis of current preservation techniques for fruits and vegetables, meat, fish, dairy, and grain, identifying key mistakes and challenges and proposing effective solutions. Feasibility tests for implementing these innovative approaches are also presented. A well-rounded study of the various causes of food waste in developing nations, this book plays a key role in bringing effective food preservation methods to the developing world. Food Preservation in Developing Countries: Challenges and solutions studies common food preservation techniques for fruits and vegetables, fish, meat, dairy, and grains, pinpointing the areas where waste occurs due to transportation, contamination, and low quality post processing. Innovative potential solutions are presented, including the feasibility of implementation of these advanced preservation techniques. The book takes a critical look at barriers to proper food preservation in these regions and offers practical solutions which can be implemented in a cost effective and timely manner. With almost one third of the world's food supply wasted each year and 13% of the world's inhabitants going hungry, this is an incredibly important and timely text. .
Introduction -- Food wastes in developing countries -- seasonal fruits and vegetables -- Low-quality post processing -- transportation -- Common food preservation techniques -- Fruits and vegetable preservation -- Fish preservation -- Meat preservation -- Dairy preservation -- Grain storage -- Effectiveness of the preservation techniques -- Contamination -- Low self-life -- Challenges in food preservation sector -- Common mistakes in preservation systems -- Possible solutions of preservation system -- Unhygienic preservation techniques -- Feasibility of implementation of advanced preservation technique -- Conclusion.
Keywords: Food science; Agriculture; Food -- Microbiology; Food Science; Agriculture; Food Microbiology